Did students learn less during the COVID-19 pandemic? Reading and mathematics competencies before and after the first pandemic wave. Issue 4 (2nd October 2022) - Schult, Johannes; Mahler, Nicole; Fauth, Benjamin; Lindner, Marlit A.
ABSTRACT: The COVID-19 pandemic disrupted classes in spring 2020. Temporary school closures supposedly led to a considerable learning loss, particularly for low-achieving students. Teachers faced challenges of remote learning environments. Students spent less time learning. The present study investigates the competencies of fifth graders in Baden-Württemberg, Germany, using large-scale assessments in reading and mathematics from annual mandatory tests in September (each n > 80, 000). Competence scores were slightly lower in 2020 (after 2 months of school closures) compared with the three previous years (–0.07 SD for reading comprehension, –0.09 for operations, and –0.03 for numbers). Regarding mathematics, low-achieving students seem to have a learning backlog that deserves attention in future education. School characteristics such as the average sociocultural capital and the proportion of students with a migration background played a minor role in mediating the schools' learning loss. Still, lower sociocultural capital was positively associated with larger learning loss in mathematics.